The Impact of Participatory Leadership on the Formation of Organizational Culture in Islamic Educational Institutions - Saputra, Reza Aprian; Citriadin, Yudin; Rahman, Hamdi (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This article analyze impact leadership participatory to formation culture organization in the institution Islamic education. Leadership participatory emphasize importance involvement all over member in the process of taking decisions, which have an impact significant in strengthening culture organization. In the institution Islamic education, culture strong organization​ play a role important in create conducive environment​ For learning, with emphasize values Islam like honesty, work same, and responsibility answer. Through approach participatory, leader No only increase engagement and loyalty employees, but also creates atmosphere inclusive and productive work . This article use method studies literature For explore connection between leadership participatory and culture organization, as well as the impact to performance institution Islamic education. Analysis results show that leadership participatory can strengthen culture organization based on Islamic values, which in turn increase effectiveness and performance institution in a way overall.